Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0069672
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dendritic Spine Density and Tau Expression Are Associated with Individual Differences in Steroidal Regulation of Male Sexual Behavior

Abstract: Male sexual behavior (MSB) is modulated by gonadal steroids, yet this relationship is highly variable across species and between individuals. A significant percentage (∼30%) of B6D2F1 hybrid male mice demonstrate MSB after long-term orchidectomy (herein after referred to as “maters”), providing an opportunity to examine the mechanisms that underlie individual differences in steroidal regulation of MSB. Use of gene expression arrays comparing maters and non-maters has provided a first pass look at the genetic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Because previous studies determined that increased APP, tau, and synaptophysin expression levels in the MPOA of B6D2F1 hybrid male mice were associated with steroid-independent male sexual behavior, we analyzed levels of these proteins in not only the B6D2F1 maters and non-maters, but their male offspring as well (Bharadwaj et al, 2013; Park et al, 2010). In concordance with previously reported results, Western blots of APP, tau, and synaptophysin from MPOA tissues showed that all three proteins were significantly higher in B6D2F1 maters relative to those in B6D2F1 non-maters [(p<0.05 for all comparisons; Figure 2A–C; APP: F-value ( 1,8 ) = 7.034, p < 0.05, η 2 =0.88; tau: F-value ( 1,8 ) = 8.476, p < 0.05, η 2 =0.94; synaptophysin: F-value ( 1,8 ) = 5.764, p < 0.05, η 2 =0.72].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because previous studies determined that increased APP, tau, and synaptophysin expression levels in the MPOA of B6D2F1 hybrid male mice were associated with steroid-independent male sexual behavior, we analyzed levels of these proteins in not only the B6D2F1 maters and non-maters, but their male offspring as well (Bharadwaj et al, 2013; Park et al, 2010). In concordance with previously reported results, Western blots of APP, tau, and synaptophysin from MPOA tissues showed that all three proteins were significantly higher in B6D2F1 maters relative to those in B6D2F1 non-maters [(p<0.05 for all comparisons; Figure 2A–C; APP: F-value ( 1,8 ) = 7.034, p < 0.05, η 2 =0.88; tau: F-value ( 1,8 ) = 8.476, p < 0.05, η 2 =0.94; synaptophysin: F-value ( 1,8 ) = 5.764, p < 0.05, η 2 =0.72].…”
Section: Resultsmentioning
confidence: 99%
“…We now have a list of candidate genes that are differentially expressed in the MPOA that correlate with steroid-independent male sexual behavior, and this list is essential towards identifying the chromosomal loci allelic distribution pattern for steroid-independent male sexual behavior (Bharadwaj et al, 2013; Park et al, 2010). It would be of interest to determine in future studies whether the BXB 1 maters also demonstrate a similar pattern of gene expression in the MPOA that correlates with steroid-independent male sexual behavior, as it would provide further evidence for the heritability of this behavioral phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations